PEMBERDAYAAN ANAK PANTI ASUHAN DALAM MENJAGA KESEHATAN LINGKUNGAN DI PANTI ASUHAN AR-RAHIM PEKANBARU - Endang Purnawati Rahayu; Herianto Herianto; Yessi Harnani (Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
Ar-Rahim Orphanage is one of the orphanages in Pekanbaru City. The problems that occur in this orphanage are the lack of children's knowledge about environmental health in orphanages and the lack of monitoring of environmental conditions. The purpose of this community service is to increase orphanage children's knowledge about environmental health and empower orphanage children as environmental health peer counselors who can motivate their friends to maintain environmental health independently. The results of this community service are an increase in orphanage children's knowledge about environmental health after counseling as seen from the pre-test and post-test results. The peer counselor program succeeded in empowering orphanage children to become role models in maintaining environmental health. Children not only receive direct benefits, but also play an active role in maintaining cleanliness in the orphanage environment. So it needs supervision from the orphanage manager so that orphanage children want to play a role in maintaining environmental health at the Ar-Rahim Pekanbaru orphanage.